Sexually Transmitted Infections in Women Participating in a Biomedical Intervention Trial in Durban: Prevalence, Coinfections, and Risk Factors. (3rd November 2013) - Abbai, Nathlee Samantha; Wand, Handan; Ramjee, Gita
Abstract : Background . Sexually transmitted infections (STIs) continue to be a significant public health problem especially among women of reproductive age in Africa. Methods . A total of 2236 women that had enrolled in the MDP301 vaginal microbicide trial were tested for the presence of Chlamydia trachomatis (CT), Neisseria gonorrhea (NG), Treponema pallidum, and Trichomonas vaginalis (TV). Results . CT was identified as the most prevalent STI (11%) followed by TV (10%), NG, and Syphilis (3%). The highest prevalence of coinfection was reported between T. pallidum and TV (19.67%, P = 0.004 ), followed by CT and TV (13.52%, P ≤ 0.001 ). Risk factors that were significantly associated with STI acquisition were women of 23 years of age or younger (HR: 1.50, 95% CI 1.17, 1.93), baseline STI with CT (HR: 1.77, 95% CI 1.32, 2.35), TV (HR: 1.58, 95% CI, 1.20, 2.10), and T. pallidum (HR: 5.13, 95% CI 3.65, 7.22), and a low education level (HR: 1.30, 95% CI 1.02, 1.66). Conclusion . Young women with lower education and a history of STIs are at high risk of multiple STIs. Prevention programs should consider target approach to STI prevention among young women. This trial is registered withISRCTN64716212 .